Conceptual framework for living with and beyond cancer: A systematic review and narrative synthesis. Issue 5 (25th March 2019) - Le Boutillier, Clair; Archer, Stephanie; Barry, Claire; King, Alex; Mansfield, Louise; Urch, Catherine
Abstract: Objective: The concept of living with and beyond cancer is now emerging in policy and literature. Rather than viewing this notion simply as a linear timeline, developing an agreed understanding of the lived experience of people affected by cancer will aid the development of person‐centred models of care. Methods: A systematic review was conducted. The review question was "What does the term 'living with and beyond cancer' mean to people affected by cancer?" The protocol for the review was preregistered in the PROSPERO database (PROSPERO CRD42017059860). All included studies were qualitative, so narrative synthesis was used to integrate descriptions and definitions of living with and beyond cancer into an empirically based conceptual framework. Results: Out of 2345 papers that were identified and 180 that were reviewed, a total of 73 papers were included. The synthesis yielded three interlinked themes: Adversity (realising cancer), Restoration (readjusting life with cancer), and Compatibility (reconciling cancer), resulting in the ARC framework. Conclusions: Three themes describe the experience of living with and beyond cancer: adversity, restoration, and compatibility. The ARC framework provides an empirically informed grounding for future research and practice in supportive cancer care for this population.